FAMILY PSYCHOLOGICAL SUPPORT DURING THE CHILD'S INPATIENT TREATMENT (BY THE EXAMPLE OF AN UROANDROLOGY DEPARTMENT) - N. V. Mazurova; S. P. Yatsyik; L. S. Namazova-Baranova; S. B. Lazurenko; S. M. Sharkov (Union of pediatricians of Russia, 2013)
Study aim: to study the peculiarities of parents' emotional responses to the stress caused by their child's hospitalization and operation to distinguish risk factors of losing personality potential by family members. Study participants and methods. The empirical study involved 82 parents (15 fathers and 67 mothers) and 76 children of preschool, primary school and juvenile age. A package of techniques involving analysis of medical cards, observation, structured conversation, mental stress calculation questionnaire, the "Incomplete sentences" technique, systematization of results and mathematical data treatment methods was defined. Theoretical analysis of the issue of emotional response of parents to stressful situations connected with their child's congenital malformations and the need in operative intervention was made. Results. It was shown that all members of a family as a single system are subject to stress. The reaction of parents to their child's operation depends on their personal characteristics, system of beliefs and life attitudes. Conclusions. The emotional condition of parents influences their child's psychological condition and the efficacy of treatment. Supporting the family psychologically during pre- and post-operative stages allows to reduce the level of emotional discomfort of children and their parents.